EFFECTIVE TEMPERATURE DIFFERENCES AMONG COVER TYPES IN NORTHEAST MINNESOTA - McGraw, Amanda M; Moen, Ron A; Overland, Lance G (Lakehead University, 2012)
Climate is probably one of the ultimate influences on the southern boundary of moose (Alces alces) distribution because moose are sensitive to warm temperatures in both summer and winter. In 4 different cover types in northeastern Minnesota we compared ambient temperatures to black globe temperatures that measures mean radiant temperature of the environment. The 4 cover types were mixed forest, treed bogs, coniferous forest, and deciduous forest that comprised ~85% of home ranges of radio-collared moose in northeastern Minnesota. Ambient temperature measurements taken from a weather station within the study area exceeded assumed physiological thresholds of 14 and 20º C for 50 and 33% of the study period, respectively. Black globe temperatures varied among cover types and temperature differences increased within cover types as ambient temperature increased. The greatest difference between deciduous and conifer cover was 2º C in black globe temperature and occurred during warm periods when skies were clear. The biological significance of these temperature differences is not clear and suggests the presence of alternative cooling mechanisms of cover types, such as water and possibly soil and duff layers acting as heat sinks. Use of these potential alternative cooling mechanisms should be considered in future research.